Early occurrence of drug intolerance as risk factor during follow-up in patients with acute coronary syndrome or coronary revascularization. Issue 4 (29th May 2018) - Albani, Stefano; Fabris, Enrico; Doimo, Sara; Barbati, Giulia; Perkan, Andrea; Merlo, Marco; Gatti, Giuseppe; Di Lenarda, Andrea; van't Hof, Arnoud W J; Maras, Patrizia; Sinagra, Gianfranco
Abstract: Aims: The occurrence of drug intolerance (DI) after an acute coronary syndrome (ACS) or percutaneous coronary intervention (PCI) is an important reason for quitting treatment. Nevertheless, the association between DI and major cardiac and cerebrovascular events (MACCE) is poorly reported in the literature, therefore, we analysed potential relationship between DI and MACCE (a composite of ACS, PCI, heart failure, and stroke) during follow-up. Methods and results: From 1 January 2014 to 31 December 2015, 891 consecutive patients after ACS or coronary revascularization were referred to cardiac rehabilitation (CR) programme and included in a dedicated registry where DI was analysed and treatment appropriately tailored. Three hundred and nine patients (34.7%) developed DI, 26.9% of them were female. Angiotensin-converting enzyme (ACE) inhibitors and statins were the most frequent drugs which caused DI, followed by beta-blockers and calcium channel blockers, in 13.1%, 12.8%, 7.5%, and 5.5% of patients, respectively. During a median follow-up of 18 (interquartile range 11–24) months after CR, MACCE occurred in 14.1% of patients with DI and 8.1% without DI ( P  = 0.007). At multivariable model, DI to 1 drug [odds ratio (OR) 1.8, 95% confidence interval (CI) 1.01–3.18; P  = 0.043] or to 2 drugs (OR 2.56, 95% CI 1.27–5.17; P  = 0.008) were independently associated to MACCE. Regarding the association of specific class of prognostic drugs to MACCE, only DI to ACE-inhibitors was independently associated with MACCE (OR 2.31, 95% CI 1.14–4.65; P  = 0.019). Conclusion: DI was frequently encountered in real-world clinical practice and was significantly associated with MACCE during follow-up. This study suggests that early occurrence of DI could be considered to be an adjunctive cardiovascular risk factor during secondary prevention.